Retrorectal tumors: A case series - B. Bülent MENTEŞ; Osman KURUKAHVECİOĞLU; Bahadır EGE; Ahmet KARAMERCAN; Sezai LEVENTOĞLU; Ömer YAZICIOĞLU; Mehmet OĞUZ (Turkish Journal of Gastroenterology, 2019)
-